Homogeneous Programming: Saddlepoint and Perturbation Function - LeBlanc, Gerald (Econometrica, 1977)
[This paper is concerned with the class of homogeneous programming problems. It is shown, to assure the existence of a saddlepoint for the associated Lagrangian, that some restrictions must be imposed on the degrees of homogeneity of the functions. Some properties of the perturbation function are also demonstrated.]